2010
DOI: 10.3989/scimar.2010.74n2215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper on the physiological responses of the commercial crab <i>Lithodes santolla</i> (Decapoda: Anomura) larvae

Abstract: SUMMARY: Effects of copper toxicity on zoea I of Lithodes santolla (Decapoda: Anomura) were analysed. The 96-h LC 50 was estimated, resulting in 298.5 µg L -1 . Groups of larvae were exposed to sublethal concentrations (40, 80 and 160 µg L -1 ) for 96 h. Oxygen consumption, ammonia excretion, O:N atomic ratio, lipid peroxidation (LPO) and body water content were measured. Oxygen consumption of treated groups (mean 46.92 ± 8.03 µg-atom O 2 h -1 mg -1 ) did not differ significantly with control. Ammonia excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The 96-h LC 50 values of copper for E. sinensis larvae were 0.16 and 0.21 mg L -1 at different growth stages, respectively. Copper toxicity for E. sinensis was of the same order of magnitude as for other crustacean larvae (Munshi et al 1996, Ferrer et al 2003, Amin and Comoglio 2010. The results obtained in this study showed that the lethal effects of copper were greater for zoea 1 larvae, suggesting that these larvae are more sensitive than megalopa larvae to water-borne copper.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The 96-h LC 50 values of copper for E. sinensis larvae were 0.16 and 0.21 mg L -1 at different growth stages, respectively. Copper toxicity for E. sinensis was of the same order of magnitude as for other crustacean larvae (Munshi et al 1996, Ferrer et al 2003, Amin and Comoglio 2010. The results obtained in this study showed that the lethal effects of copper were greater for zoea 1 larvae, suggesting that these larvae are more sensitive than megalopa larvae to water-borne copper.…”
Section: Discussionsupporting
confidence: 64%
“…Oxygen consumption and other indices related to respiration and metabolism have been used to assess physiological responses under various stressful environments in decapod crustaceans , Dissanayake et al 2008, Amin and Comoglio 2010. High oxygen consumption and RQs after copper exposure have been attributed to ultrastructural damage to the gill epithelium (Yang et al 2007), and their increases reflect an extra metabolic demand in copper-exposed animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several indexes related to metabolism, such as oxygen consumption, have been used to assess physiological responses in decapods under various stressful pollutants and situations (Amin and Comoglio, 2010;Comoglio et al, 2008;Spice and Weber, 1991). However, oxygen consumption and ammonia excretion in crustaceans are affected by several extrinsic factors such as temperature, dissolved oxygen, ambient ammonia concentration, salinity and pH (Chen and Lee, 1997;Chen and Lin, 1995;Jiang et al, 2000;Kemp et al, 2009;Regnault, 1987).…”
Section: Introductionmentioning
confidence: 99%